(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
The symptomatology of Gridhrasi given in Ayurvedic classics are pain in chronological order starting from Sphikpurva, Kati, Prushta, Uru, Janu, Jangha, upto Pada, Sakthna kshepo nighruniyat. The clinical features of lumbar spondylosis can be correlated with Gridhrasi and condition can be treated on the lines of Gridhrasi and Vatavyadhi. Objectives: To evaluate the efficacy of Katibasti, Ksheerabasti and Vatagajankusha rasa as Shamanoushadhi in the management of Gridhrasi vis a vis lumbar spondylosis. Result: The therapies Katibasti, Ksheerabasti and Vatagajankusha rasa along with the suitable Anupana as Shamanoushadhi chosen for the treatment showed very good results in terms of reducing acute pain as well as radiculopathy. Conclusion: As the long term or extensive use of NSAID’s, Cox-inhibitors like etoricoxib, muscle relaxants, intervertebral steroid injections and even surgery in the management of lumbar spondylosis will induce serious adverse effect on body, safe and effective therapies like Katibasti, Ksheerabasti and Vatagajankusha rasa along with the suitable Anupana as Shamanoushadhi were selected for treatment. These therapies have not caused any adverse events and improved the condition by arresting the pathogenesis at their respective particular stages. It was observed that the above mentioned Ayurvedic therapies were found to be safe and effective in Gridhrasi vis a vis Lumbar spondylosis.